PENGARUH PENAMBAHAN KONSENTRAT DENGAN KADAR PROTEIN KASAR YANG BERBEDA PADA RANSUM BASAL TERHADAP PERFORMANS KAMBING BOERAWA PASCA SAPIH - M. Arifin; Liman .; K. Adhianto (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2012)
The aims of the research is done to study the influence of additional concentrate with the difference crude protein value on bassal ration to the performance Boerawa goat – pasca weaning. The goat used is Boerawa goat - pasca weaning was used as many as 20 goats with average beginning weight 18,25 ± 6,13 kg/goats from Gisting. This research uses randomized block design, consists of four treatments, R0= bassal ration, R1= R0 (60%) + concentrate A (40%), R2= R0 (60%) + concentrate B (40%), and R3= R0 (60%) + concentrate C (40%), with five replications. The fresh water was given Boerawa goat by ad libitum during the research. The result of the research shows: there was significant effect (P<0,01) of additional concentrate on bassal ration for the feeding consumption of Boerawa goat – pasca weaning, on the contrary there were no significant effect (P>0,05) for the increasing of body weight, protein efficiency ratio, and feeding conversion. Key word: concentrate, performance, crude protein, Boerawa goat.